Data Communication Crypto Protocol for Security Systems Sensor Networks - Bykovyy, P.; Kochan, V.; Kinakh, Y.; Sachenko, A.; Roshchupkin, O.; Aksoy, Serkan; Markowsky, G. (IEEE, 2009)
This paper describes hardware implementations of crypt protocol elements for secured data communication in two wired networks of security system detectors. Those elements are basic to crypto protocol development for that type of network. In addition, hardware tools for the network controller and the network server that support this protocol were developed. These tools will allow us to test and debug the proposed security elements and the crypt protocol.
5th IEEE International Workshop on Intelligent Data Acquisition and Advanced Computing Systems - Technology and Applications (IDAACS) -- SEP 21-23, 2009 -- Rende, ITALY
Keywords: security systems; sensor networks; crypto protocol; microcontroller